Arbitrary hybrid turbulence modeling approach for high-fidelity NREL phase VI wind turbine CFD simulation - Kamalov, Bagdaulet (2023)
Today, growth in renewable energy is increasing, and wind energy is one of the key renewable energy sources which is helping to reduce carbon emissions and build a more sustainable world. Developed countries and worldwide organizations are investing in technology and industrial application development. However, extensive experiments using wind turbines are expensive, and numerical simulations are a cheaper alternative for advanced analysis of wind turbines. The aerodynamic properties of wind turbines can be analyzed and optimized using CFD tools. Currently, there is a general lack of available high-fidelity analysis for the wind turbine design community. This study aims to fill this urgent gap. In this paper, an arbitrary hybrid turbulence model (AHTM) was implemented in the open-source code OpenFOAM and compared with the traditional URANS model using the NREL Phase VI wind turbine as a benchmark case. It was found that the AHTM model gives more accurate results than the traditional URANS model. Furthermore, the results of the VLES and URANS models can be improved by improving the mesh quality for usage of higher-order schemes and taking into consideration aeroelastic properties of the wind turbine, which will pave the way for high-fidelity concurrent multidisciplinary design optimization of wind turbines.